Risk factors for musculoskeletal disorders among takeaway riders: Up-to-date evidence in Shanghai, China - Li, Ziyun; Bo, Xiaochen; Qian, Chen; Chen, Mingyue; Shao, Yuqing; Peng, Yuxun; Cai, Ruian; Huang, Xiaojing; Wei, Lijun; Zhao, Jinzhong; Shi, Jianwei (Frontiers in Public Health, 2022)
Background: Musculoskeletal disorders (MSDs) are common occupational diseases. However, the influencing mechanisms were not clear in the new emerging takeaway rider occupation in the catering industry in China. Methods: A cross-sectional study was conducted using a takeaway rider sample from one of the largest e-platforms, the Mei Tuan Company in Shanghai. The chi-square test was used to compare the sex differences in MSDs according to various factors. Binary logistic regressions were then performed to explore the potential risk factors for the occurrence and severity of MSDs adjusted by age, sex and vehicle type. Crude odds ratios (CORs) and adjusted odds ratios (AORs) and their 95% conﬁdence intervals (CIs) for predictors were reported. Results: The prevalence of MSDs was found to be 54.94% (n=361). Shoulders (joint pain: 24.5%, n=154/629 cases; muscle pain: 29.0%, n=183/632 cases; muscle numbness: 31.7%, n=120/379 cases) and neck (joint pain: 17.0%, n=107/629 cases; muscle pain: 14.1%, n=89/632 cases; muscle numbness: 15.3%, n=58/379 cases) were the most affected regions. Irregular meals (often having regular meals: p=0.03, AOR=1.89, 95% CI: 1.05 3.39; sometimes: p<0.01, AOR=2.54, 95% CI: 1.49 4.34 and seldomly: p<0.01, AOR=4.24, 95% CI: 2.28 7.91) were positively associated with the occurrence of MSDs. Work-related factors, including working over 5 years (p=0.02, AOR=1.87, 95% CI: 1.10 3.17) and over 51 km of food delivery distance per day (51 75 km: p=0.02, AOR=2.13, 95CI%:1.13 4.01; ≥76 km: p<0.01, AOR=3.12, 95CI%: 1.44 6.77), were strongly associated with severity. Conclusion: MSDs were common among takeaway riders. Personal lifestyles (meal irregularity) were found to predict the occurrence, while work-related factors (longer years of employment and prolonged food delivery distance) were positively associated with severity. Public health efforts should be made to prevent MSDs in this population.